Production of microbial keratinase using newly isolated strain of Stenotrophomonas maltophilia its characterization and applications. - Parmar, Bhavika; Trivedi, Sneha (Kuwait Journal of Science, 2021)
Biodegradation of keratin rich wastes such as chicken feathers, nails, hairs and wool, is an environment friendly biotechnological process, which converts this abundant waste into low-cost, nutrient rich animal feed. It is a sustainable green approach towards the solution of environmental threats created by these wastes. The aim of this study was screening of potential keratinase degrading microorganisms and optimization of their ability to feather degradation by keratinase production and its application. Four different poultry farm soil samples were collected from surat for this study. These four different soil samples were serially diluted and enriched for keratinase producer in whole feather basal medium. Among these samples, 16 isolates showed keratinolytic activity in primary screening using skim milk agar plate. 9 isolates out of 16, showed keratinolytic activity in secondary screening using keratin agar plate. The isolate (KA1a) giving the highest yield was identified as a strain of Stenotrophomonas maltophilia (NCBI Accession number MT478451), based on biochemical characteristics and 16s rRNA sequence analysis. The isolate exhibited maximum keratinase production (108 U/ml) in optimized feather basal medium containing feathers (2.2%), NaCl (0.5%), K2HPO4 (0.3%), KH2PO4 (0.4%), pH7, inoculated with 10% v/v pre-grown cell mass and incubated at 37°C on rotary shaker for 24hrs. The keratinase enzyme was partially purified and characterized. Maximum enzyme activity was observed at 40°C and pH7.0. The enzyme showed potential applications as detergent additive, animal feed and organic fertilizer.